Big Enough for an Aromatase Inhibitor? How Adiposity Affects Male Fertility - Stephens, Sahar M.; Polotsky, Alex J. (Seminars in Reproductive Medicine, 2013)
Obesity is a pandemic and is associated with multiple medical problems including subfertility. Male obesity has been associated with altered semen parameters and reproductive hormonal levels, including a reduced testosterone:estradiol (T:E2) ratio. Treatment methods employed for obesity-related male subfertility include gonadotropin administration, weight loss, and aromatase inhibitors. Letrozole is a highly effective nonsteroidal aromatase inhibitor that has been used to treat male subfertility in several case series with promising results. Adequately designed randomized controlled studies are needed to produce evidence-based data on the role of aromatase inhibitors in male subfertility management and evaluate the side-effect profile.
Keywords: male obesity; infertility; aromatase inhibitor; letrozole